To Check the Effect of Advertising, Personal Selling and Public Relations on Consumer Preferences, A Case of Telecommunication Sector in Faisalabad (International Journal of Management and Sustainability, 2017)
In this hyper competitive contemporary world, the organizations are focusing on consumer’s preferences which had been a significant sphere of research for researchers. The organizations are combating in this field to measure the preferences of the consumers through different marketing techniques. Even though firms are investing heavy amount of their capital on these techniques and tools rather they need assurance to invest the amount on what sort of marketing communication tools for the purpose of attaining the preferences of consumers. To explore this broad area, research was conducted by investigating the impact of communication mix activities on consumer’s preferences. The advertisement, personal selling and public relation were taken as independent variables and their impact was regressed on consumer’s preferences, the dependent variable. The convenience sampling technique was used because the population size was large and easily accessible and respondents were 323. The industry targeted was telecommunication sector of Faisalabad. The results of the research showed that the P value of consumer’s preferences was significant at p value 0,002, the P values of independent variables, advertising was 0.046, personal selling was 0.000 and public relation was 0.000. The research showed significant relationship between independent and dependent variables.